Functional characterization of Ostreococcus tauri phototropin. Issue 2 (28th September 2015) - Sullivan, Stuart; Petersen, Jan; Blackwood, Lisa; Papanatsiou, Maria; Christie, John M.
Summary: Phototropins (phots) regulate a range of adaptive processes in plants that serve to optimize photosynthetic efficiency and promote growth. Light sensing by Arabidopsis thaliana phots is predominantly mediated by the Light, Oxygen and Voltage sensing 2 (LOV2) flavin‐binding motif located within the N‐terminus of the photoreceptor. Here we characterize the photochemical and biochemical properties of phot from the marine picoalga Ostreococcus tauri phototropin (Otphot) and examine its ability to replace phot‐mediated function in Arabidopsis . Photochemical properties of Otphot rely on both LOV1 and LOV2. Yet, biochemical analysis indicates that light‐dependent receptor autophosphorylation is primarily dependent on LOV2. As found for Arabidopsis phots, Otphot associates with the plasma membrane and partially internalizes, albeit to a limited extent, in response to blue‐light irradiation. Otphot is able to elicit a number of phot‐regulated processes in Arabidopsis, including petiole positioning, leaf expansion, stomatal opening and chloroplast accumulation movement. However, Otphot is unable to restore phototropism and chloroplast avoidance movement. Consistent with its lack of phototropic function in Arabidopsis, Otphot does not associate with or trigger dephosphorylation of the phototropic signalling component Non‐Phototropic Hypocotyl 3 (NPH3). Taken together, these findings indicate that the mechanism of action of plant and evolutionarily distant algal phots is less well conserved than previously thought.